2015
DOI: 10.1890/es15-00140.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of the nitrogen‐fixing lichen Lobaria pulmonaria to phosphorus, molybdenum, and vanadium

Abstract: Abstract. Nitrogen-fixing lichens (cyanolichens) are an important source of nitrogen (N) in Pacific Northwest forests, but limitation of lichen growth by elements essential for N fixation is poorly understood. To investigate how nutrient limitation may affect cyanolichen growth rates, we fertilized a tripartite cyanobacterial lichen (Lobaria pulmonaria) and a green algal non-nitrogen fixing lichen (Usnea longissima) with the micronutrients molybdenum (Mo) and vanadium (V), both known cofactors for enzymes invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…cyanolichens in Oregon, US (Horstmann et al 1982). However, a more recent study on Lobaria and Usnea cyanolichens from the same region (Oregon) reported no effect of Mo addition on BNF (Marks et al 2015b). High spatiotemporal variability in Mo limitation, which has been reported in leaf litter and cryptogams (Jean et al 2013;Rousk et al 2017;Wurzburger et al 2012), may explain some of the discrepancies between these two studies.…”
Section: Terrestrial Environments-soilsmentioning
confidence: 94%
See 1 more Smart Citation
“…cyanolichens in Oregon, US (Horstmann et al 1982). However, a more recent study on Lobaria and Usnea cyanolichens from the same region (Oregon) reported no effect of Mo addition on BNF (Marks et al 2015b). High spatiotemporal variability in Mo limitation, which has been reported in leaf litter and cryptogams (Jean et al 2013;Rousk et al 2017;Wurzburger et al 2012), may explain some of the discrepancies between these two studies.…”
Section: Terrestrial Environments-soilsmentioning
confidence: 94%
“…Unfortunately, trace metals are not routinely included in soil and litter analyses, which often focus on C and N. When trace metals are reported, Mo and especially V are rarely considered, except in studies on contaminated soils (Johnson and Hale 2004;Lawrey 1978). In addition, datasets on trace metal concentrations in terrestrial samples must be examined carefully, as sample preparation for elemental analysis must avoid metal-based equipment, such as steel Wiley mills and roller grinders, which can be a source of metal contamination (Marks et al 2015b). Mo is particularly sensitive to contamination during sample preparation due to its low environmental concentrations and its presence is numerous metal alloys.…”
Section: Inclusion Of Trace Metals In Organic Matter Analysesmentioning
confidence: 99%
“…particles, canopy flow‐through) are the main sources of metals (e.g. V and Mo) to lichens (Darnajoux et al ., ; Marks et al ., ), we postulated that, along a vegetative succession, the amount of Mo and V, as well as the relative Mo : V ratio, might vary significantly as a result of different canopy openness and vegetation composition. A fire chronosequence might thus provide samples growing under similar climatic and geological conditions, but with contrasted Mo and V exposures.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier laboratory experiments, relative growth rate was measured in discs cut from lichens (Scott 1956, 1960; Pearson 1970), while others dealt with whole lichen thalli (Kershaw & Millbank 1969; Pearson & Benson 1977). In recent years, growth experiments have increasingly been used to investigate the effects of environmental impacts on entire lichens in field (Hyvärinen & Crittenden 1998; Cooper & Wookey 2001; Gauslaa et al 2006, 2007; McCune & Caldwell 2009; Yemets et al 2014; Marks et al 2015) and laboratory studies (Cooper et al 2001; Bidussi et al 2013; Alam et al 2015). By integrating important processes, lichen growth is among the most robust measures of lichen performance and viability.…”
Section: Introductionmentioning
confidence: 99%